Catheter-induced infectious endocarditis complicated by pulmonary embolism: successful surgical treatment - A. P. Medvedev; S. A. Fedorov; V. V. Pichugin; A. L. Maksimov; M. B. Sukhova; A. V. Bogush; Q. B. Vepaev (Вестник хирургии имени И.И. Грекова, 2020)
A rare case of catheter-induced infectious endocarditis of the right heart chambers complicated by embolism of the left pulmonary artery and its successful surgical treatment is presented. We performed the operation to remove a foreign body and vegetations from the superior vena cava and the right atrium, embolectomy from the left main branch of the pulmonary artery, chemical sanitation of the right chambers of the heart and pulmonary artery under extracorporeal circulation.